Penyelarasan Kompetensi Digital Marketing SMKN 1 Purwokerto dengan Kebutuhan Industri - Muhammad Eka Purbaya; Prasetyo Hartanto; Satya Fajar Gumelar; Bening Dwi Sasmita (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
The rapid growth of digital marketing has increased the demand for a competent workforce, while many vocational school teachers still face limitations in both theoretical understanding and practical implementation of digital marketing practices. This community service program aimed to strengthen the digital marketing competencies of 15 teachers at SMKN 1 Purwokerto through workshops facilitated by certified lecturers and industry practitioners. The program applied a participatory and collaborative approach consisting of needs analysis, workshop sessions, curriculum realignment, industry-based module development, and continuous mentoring over six months. The findings showed significant improvements in teachers’ competencies, with an 82.6% increase in digital marketing comprehension scores, rising from 45.3 to 82.6. In addition, all participating teachers successfully mastered innovative lesson planning and the implementation of digital marketing tools in classroom learning. The program also produced eight validated industry-based learning modules, exceeding the initial target. Furthermore, 87% of teachers who were interested in professional certification successfully obtained certification. The results indicate that collaboration between academics and industry practitioners effectively enhances vocational teachers’ competencies and provides a replicable model for improving the quality and industry relevance of vocational education in the digital era.